A few laps with Bill Sweetenham - Goldsmith, W. (1999)
Bill Sweetenham, a living legend of Australian Swimming and current National Youth Coach for Australian Swimming answers some questions on swimming and his work. - Why, where and how did you get involved in coaching? - You have been involved with some of our greatest ever swimmers. Are there common characteristics that you have seen in all champion swimmers? - How important are good technique and skills to swimming success? - What role do you think parents should play in the development of their kids swimming career? - What is your role with Australian Swimming today? - How do kids balance school, life and competition swimming? - As National Youth Coach, do you see as much talent around Australia today as there was in the past? - If you were 25 - 30 years of age and starting your coaching career from scratch, how would you attack it? - If you could give one piece of advice to kids training hard to make it to Sydney 2000 what would it be?